Real-Time Three-Dimensional Echocardiography in Percutaneous Transcatheter Closure of Atrial Septal Aneurysm with Atrial Septal Defect in Pediatrics - Mohamed Yehia Eldeeb, Rawan Mohamed; Rasol Toulba, Osama Abd Rab El; El Sheikh, Raghda Ghonimy; Elshehaby, Walid Ahmed; Adel, Hani Mahmoud (Journal of Neonatal Surgery, 2025)
Background: ASA (atrial septal aneurysm) is redundant and mobile atrial septum. It accounts for 2-3% of population. Aim: This study aims to evaluate the use of echocardiographic guidance in percutaneous closure of ASA. Methods: It is a prospective cohort design on 60 ASD secondum children who were referred for transcatheter closure between february 2022 to february 2024 at catheterization labs of Tanta Teaching University Hospital, Tanta New Surgical Hospital and Alexandria Smouha Children University Hospital. Results: Only 14 ASD cases were ASD with ASA and all underwent percutaneous closure successfully with different closure techniques with no risk of complications and deployment was done smoothly under three-dimensional echocardiography. Conclusions: Three-dimensional echocardiography can help in closure of secondum ASD with ASA in children